2-phenylacetamide Separated from the seed of Lepidium apetalum Willd. inhibited renal fibrosis via MAPK pathway mediated RAAS and oxidative stress in SHR Rats - Pei-pei Yuan; Meng Li; Qi Zhang; Meng-nan Zeng; Ying-ying Ke; Ya-xin Wei; Yang Fu; Xiao-ke Zheng; Wei-sheng Feng (BMC, 2023)
Abstract Background Renal fibrosis with Renin-angiotensin-aldosterone system (RAAS) activation and oxidative stress are one of the major complications in hypertension. 2-phenylacetamide (PA), a major active component of Lepidium apetalum Willd. (L.A), has numerous pharmacological effects. Its analogues have the effect of anti-renal fibrosis and alleviating renal injury. This study aims to explore the underlying mechanism of PA for regulating the renal fibrosis in SHR based on the MAPK pathway mediated RAAS and oxidative stress. Methods The SHR rats were used as the hypertension model, and the WKY rats were used as the control group. The blood pressure (BP), urine volume were detected every week. After PA treatment for 4 weeks, the levels of RAAS, inflammation and cytokines were measured by Enzyme-Linked Immunosorbnent Assay (ELISA). Hematoxylin-Eosin staining (HE), Masson and Immunohistochemistry (IHC) were used to observe the renal pathology, collagen deposition and fibrosis. Western blot was used to examine the MAPK pathway in renal. Finally, the SB203580 (p38 MAPK inhibitor) antagonism assay in the high NaCl-induced NRK52e cells was used, together with In-Cell Western (ICW), Flow Cytometry (FCM), High Content Screening (HCS) and ELISA to confirm the potential pharmacological mechanism. Results PA reduced the BP, RAAS, inflammation and cytokines, promoted the urine, and relieved renal pathological injury and collagen deposition, repaired renal fibrosis, decreased the expression of NADPH Oxidase 4 (NOX4), transforming growth factor-β (TGF-β), SMAD3 and MAPK signaling pathway in SHR rats. Meanwhile,,the role of PA could be blocked by p38 antagonist SB203580 effectively in the high NaCl-induced NRK52e cells. Moreover, molecular docking indicated that PA occupied the ligand binding sites of p38 MAPK. Conclusion PA inhibited renal fibrosis via MAPK signalling pathway mediated RAAS and oxidative stress in SHR Rats.